Acute disseminated encephalomyelitis following completion of pneumococcal meningitis treatment: A case report and review of the literature - Özel, Ayşe Serra; Altunal, Lütfiye Nilsun; Sakcı, Zakir; Yılmaz, Ece Aslı; Yılmaz, Mesut; Kadanalı, Ayten (Galenos Publishing House, 2023)
Acute disseminated encephalomyelitis (ADEM) is an immune-mediated inflammatory disease of the central nervous system (CNS) and is commonly seen in children. It has seasonal peaks in winter and spring, consistent with its infectious etiologies, and it rarely occurs as a reaction to vaccination. ADEM is less common in adults and progresses with a more severe clinical course. Cases diagnosed with ADEM by CNS demyelination after streptococcal meningitis have rarely been reported in adult patients. In this report, we present a rare case of a 31-year-old female diagnosed with ADEM following pneumococcal meningitis treatment and treated successfully with low-dose methylprednisolone.

Akut dissemine ensefalomiyelit (ADEM), merkezi sinir sistemini etkileyen immün sistem ilişkili enflamatuvar bir hastalık olup sıklıkla çocuklarda görülür. Enfeksiyöz etiyolojiler ile ilişkili olması sebebiyle sonbahar ve kış dönemlerinde mevsimsel pik yapmakta olup nadiren aşılara karşı bir reaksiyon olarak da görülmektedir. Akut dissemine ensefalomiyelit erişkinlerde daha nadir görülmekte ve daha ağır bir klinik tabloya sebep olmaktadır. Erişkin hastalarda nadiren streptokoksik menenjit sonrası merkezi sinir sistemi demiyelinizasyonu ile ADEM tanısı konulan olgular bildirilmiştir. Bu yazıda pnömokokal menenjit tedavisini takiben ADEM tanısı alan ve düşük doz metilprednizolon ile başarılı bir şekilde tedavi edilen 31 yaşında bir kadın olgu sunulmuştur.
Pnömokokal menenjit tedavisinin tamanlanmasını takiben gelişen akut dissemine ensefalomiyelit: Olgu sunumu ve literatür taraması
Keywords: Acute Disseminated Encephalomyelitis; ADEM; Meningitis; Streptococcus Pneumoniae; Akut Dissemine Ensefalomiyelit; ADEM; Menenjit; Streptococcus Pneumoniae